The Utility of SAPROF-YV Ratings for Predicting Recidivism in Male Youth Under Community Supervision in Singapore - Chu, Chi Meng (Criminal justice and behavior, 2020)
There is bourgeoning empirical support for the usage of the Structured Assessment of Protective Factors (SAPROF) across many jurisdictions, but there is a dearth of research on the Structured Assessment of Protective Factors for Violence Risk—Youth Version (SAPROF-YV). This study examined (a) the predictive validity of the SAPROF-YV ratings for general recidivism and (b) the incremental predictive validity of the SAPROF-YV ratings when used in conjunction with the Youth Level of Service/Case Management Inventory (YLS/CMI) 2.0 ratings. Using a sample of 822 male youths who were involved with the justice system and under community supervision in Singapore, the results showed that the SAPROF-YV total score and final protection judgment rating were significantly predictive of general recidivism. Moreover, the SAPROF-YV total score and final judgment rating showed incremental predictive validity over the YLS/CMI 2.0 total score and risk rating. Overall, the results suggest that SAPROF-YV ratings are suited for assessing justice-involved youth within the Singaporean context and can be used in conjunction with YLS/CMI 2.0 ratings for predicting recidivism.